Pre-exposure of abundant species to disturbance improves resilience in microbial metacommunities - Cairns, Johannes; Hogle, Shane; Alitupa, Elizaveta; Mustonen, Ville; Hiltunen, Teppo (Nature Publishing Group, 2025)
Understanding factors influencing community resilience to disturbance is critical for mitigating harm at various scales, including harm from medication to gut microbiota and harm from human activity to global biodiversity, yet there is a lack of data from large-scale controlled experiments. Factors expected to boost resilience include prior exposure to the same disturbance and dispersal from undisturbed patches. Here we set up an in vitro system to test the effect of disturbance pre-exposure and dispersal represented by community mixing. We performed a serial passage experiment on a 23-species bacterial model community, varying pre-exposure history and dispersal rate between three metacommunity patches subjected to different levels of disturbance by the antibiotic streptomycin. As expected, pre-exposure caused evolution of resistance, which prevented decrease in species abundance. The more abundant the pre-exposed species had been in the undisturbed community, the less the entire community changed. Pre-exposure of the most dominant species also decreased abundance change in off-target species. In the absence of pre-exposure, increasing dispersal rates caused increasing spread of the disturbance across the metacommunity. However, pre-exposure kept the metacommunity close to the undisturbed state regardless of dispersal rate. Our findings demonstrate that pre-exposure is an important modifier of ecological resilience in a metacommunity setting.